Avaliação do desempenho de gabiões eletrossoldados com diferentes materiais de preenchimento para aplicações em infraestrutura sustentável - Rocha, Cleyton Vicente (2025)
Welded mesh gabions have been increasingly used in geotechnical and urban applications due to their structural rigidity, ease of assembly, and ability to accommodate different filling materials. Despite their growing adoption, studies on their mechanical behavior remain limited, particularly in Brazil. Therefore, this research analyzed the technical and structural feasibility of using different filling materials in welded mesh gabion modules, comparing their performance under simple compression. For this purpose, gabions filled with compacted medium sand and #2 gravel were studied, previously characterized in terms of particle size distribution and specific weight. The tests were conducted on experimental modules of 0.4 × 0.4 × 0.4 m, in which compressive strength, horizontal and vertical deformations, as well as secant, tangent, and stiffness moduli were analyzed. Additionally, statistical analyses were performed, including the t-test to verify significant differences between the fillings and correlation determination using Pearson’s method to evaluate the relationship between the analyzed mechanical parameters. The results showed that the #2 gravel filling provided greater stability and lower deformability, evidenced by the lower variation in vertical and horizontal deformations throughout the loading process. The rigid behavior of gravel resulted in higher secant modulus and stiffness values, making this filling more suitable for structures requiring greater load-bearing capacity and lower displacement under high stresses. Conversely, gabions filled with compacted medium sand exhibited a more deformable behavior, with reduced stiffness throughout loading, reflecting higher sensitivity to applied stresses and greater variation in deformations. The statistical analyses indicated that, for some of the analyzed parameters, there was a statistically significant difference between the different fillings, confirming that the choice of material directly impacts the structural performance of the gabions. The Pearson correlation method demonstrated a significant relationship between maximum vertical stress and deformations, showing that increasing applied loads results in a distinct response depending on the filling material. Gabions filled with gravel exhibited a more linear and predictable correlation, while those filled with sand showed greater data dispersion, reinforcing the need for strict compaction control of this material to ensure more stable performance. Additionally, the stress-strain curves obtained from the compression tests are presented, which can be used as a practical tool for deformation estimates in basic designs of temporary retaining structures. These curves allow for predicting the behavior of gabions under different applied loads, aiding in the design of temporary solutions for slope stabilization, debris retention, and emergency infrastructure reinforcement. The research highlights the potential of these structures in sustainable urban infrastructure, as gabions are permeable, flexible, and resistant, characteristics that reduce hydrostatic pressure and promote environmental integration. From a sustainability perspective, this technology stands out as a dry construction method, eliminating the need for cement or mortar, reducing the consumption of natural resources, and promoting the reuse of low-impact materials. However, the use of sand and gravel as filling materials is only feasible in welded mesh gabions, due to the rigidity of the mesh, which ensures proper confinement of these granular materials. To prevent material loss through the mesh openings, the use of non-woven geotextile fabric as an internal lining is recommended. The findings of this research significantly contribute to the adoption of welded mesh gabions in geotechnical engineering and urban infrastructure projects, providing technical guidelines for their efficient and sustainable use. Furthermore, they pave the way for new investigations into the structural behavior of these structures under different loading and confinement conditions, consolidating their potential as a viable, cost-effective, and environmentally responsible alternative for soil stabilization and slope containment.